The association between intracranial pressure and optic nerve sheath diameter on patients with head trauma - Kaan Çelik; Bekir Enes Demiryurek (Arquivos de Neuro-Psiquiatria)
Abstract Background: Although intracranial pressure (ICP) monitoring is the gold standard method for measuring intracranial pressure after traumatic brain injury, optic nerve sheath diameter (ONSD) measurement with ultrasound (US) is also used in the evaluation of ICP. Objective: To investigate the association between a series of OSND measurements by US and changes in clinical presentation of the patient. Methods: Prospective study including 162 patients with traumatic brain injury. Age, sex, cerebral CT findings, ONSD levels by US at minutes 0, 60, and 120, Glasgow Coma Scale (GCS) within same period, change of consciousness, treatment, and mortality data were reviewed. The association of ONSD levels with GCS, change of consciousness, treatment, and mortality was evaluated. Results: There was no difference in ONSD changes in the patients’ sample within the period (p=0.326). ONSD significantly increased in patients who died (p<0.001), but not in those who survived (p=0.938). There was no significant change in ONSD of the patients who received anti-edema therapy (p=801), but significantly increased ONSD values were found in those who received anti-edema therapy (p=0.03). Patients without change of consciousness did not have any significant change in ONSD (p=0.672), but ONSD values increased in patients who consciousness became worse, and decreased in those who presented a recovery (respectively, p<0.001, p=0.002). A negative correlation was detected between ONSD values and GSC values measured at primary, secondary, and tertiary time periods (for all p<0.001). Conclusions: ONSD follow-up may be useful to monitor ICP increase in patients with acute traumatic brain injury.